Using Random Amplified Polymorphic DNA to Assess Genetic Diversity and Structure of Natural Calophyllum brasiliense (Clusiaceae) Populations in Riparian Forests - Evânia Galvão Mendonça; Anderson Marcos de Souza; Fábio de Almeida Vieira; Regiane Abjaud Estopa; Cristiane Aparecida Fioravante Reis; Dulcinéia de Carvalho (International Journal of Forestry Research)
The objective of this study was to assess the genetic variability in two natural populations of Calophyllum brasiliense located along two different rivers in the state of Minas Gerais, Brazil, using RAPD molecular markers. Eighty-two polymorphic fragments were amplified using 27 primers. The values obtained for Shannon index (I) were 0.513 and 0.530 for the populations located on the margins of the Rio Grande and Rio das Mortes, respectively, demonstrating the high genetic diversity in the studied populations. Nei’s genetic diversity (He) was 0.341 for the Rio Grande population and 0.357 for the Rio das Mortes population. These results were not significantly different between populations and suggest a large proportion of heterozygote individuals within both populations. AMOVA showed that 70.42% of the genetic variability is found within populations and 29.58% is found among populations (ФST=0.2958). The analysis of kinship coefficients detected the existence of family structures in both populations. Average kinship coefficients between neighboring individuals were 0.053 (P<0.001) in Rio das Mortes and 0.040 (P<0.001) in Rio Grande. This could be due to restricted pollen and seed dispersal and the history of anthropogenic disturbance in the area. These factors are likely to contribute to the relatedness observed among these genotypes.